GLP-1 RECEPTOR AGONISTS AND ALCOHOL USE DISORDER: A NARRATIVE REVIEW OF THERAPEUTIC POTENTIAL AND WELL-BEING OUTCOMES - Polek, Nina; Sikorska, Małgorzata; Mularczyk, Patrycja; Łysoniewski, Wojciech; Marcysiak, Artur; Mruzek, Tomasz; Kiełbasiewicz, Magdalena; Zawadzka, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
Alcohol use disorder (AUD) remains a major global health challenge associated with substantial morbidity, mortality, and impaired well-being, while currently approved pharmacotherapies offer only modest and heterogeneous benefits. This narrative review examines the therapeutic potential of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in AUD, with particular attention to their neurobiological rationale, emerging clinical relevance, and broader implications for health and well-being. A structured narrative search of PubMed and Google Scholar, supplemented by reference screening, identified thirty-one relevant publications spanning preclinical studies, human observational analyses, randomized controlled trials, Mendelian randomization research, and review papers. Across preclinical models, GLP-1 receptor activation consistently reduced alcohol intake, reward-related responding, and relapse-like behaviour, supporting a mechanistic role for GLP-1 signalling in the modulation of mesolimbic reward pathways, gut–brain communication, and the interface between metabolic and motivational processes. Early human studies provide a promising but still inconclusive translational signal, with some trials reporting reductions in craving and selected drinking outcomes, while pooled randomized evidence remains limited and heterogeneous. Observational findings further suggest associations between GLP-1RA use and reduced alcohol-related events, although causal inference remains restricted. Overall, GLP-1RAs represent a biologically plausible and clinically promising, but still investigational, approach to AUD. Their potential to integrate metabolic and neurobehavioral dimensions of care may be especially relevant for improving long-term health outcomes, although larger and more rigorous trials are needed to define their efficacy, safety, and place in treatment.